2019
DOI: 10.1177/0022042619871008
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Microdosing Classic Psychedelics

Abstract: Microdosing classic psychedelics (e.g., LSD [lysergic acid diethylamide] and psilocybin) is the practice of taking small amounts of these substances to bring about various positive life changes. Little is known about the subjective experiences and perceptions of those who engage in the practice. Accordingly, we use the sociology of accounts as a theoretical framework to explore the ways that those who microdose excuse or justify their practice. Using data from semistructured interviews with 30 people who had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Three qualitative studies (Anderson et al, 2019b;Beaton et al, 2020;Webb et al, 2019), and one retrospective survey study (Bright et al, 2021) showed increases in the overlapping constructs of wellbeing, self-fulfilment, self-efficacy, and resilience.…”
Section: Wellbeing and Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Three qualitative studies (Anderson et al, 2019b;Beaton et al, 2020;Webb et al, 2019), and one retrospective survey study (Bright et al, 2021) showed increases in the overlapping constructs of wellbeing, self-fulfilment, self-efficacy, and resilience.…”
Section: Wellbeing and Attitudesmentioning
confidence: 99%
“…Several studies assessed respondents' reasons for microdosing. A wide variety of motives were reported, including performance enhancement, mood enhancement, and curiosity (Hutten et al, 2019a); treatment of health conditions (Hutten et al, 2019b); selffulfilment, coping with negative situations, and increasing social connection (Beaton et al, 2020); improving mental health, personal/spiritual development, and enhancing cognitive performance (Lea et al, 2020b). In general, participants reported confidence that microdosing fulfilled these aims (e.g., Anderson et al, 2019a;Cameron et al, 2020;Petranker, Anderson, Maier, et al, 2020).…”
Section: Motives For Microdosingmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on the same data set and expanding on the findings of the above study, Beaton et al (2019) looked into how participants accounted for their microdosing to manage the potential stigma of illegal drug use. Using the conceptual framework of accounts as ways that people align their behaviors with social expectations, the authors noted participants' concern with potential negative judgment from others.…”
Section: Coordinates For Sociological Investigations Of Microdosingmentioning
confidence: 99%
“…Of the diverse and often competing forces making up the psychedelics renaissance, some of the most powerful ones that merit a closer examination are: a) growing scientific research in psychedelics following a decades-long hiatus, mainly in clinical psychiatry and neuroscience, that focuses on their therapeutic potential for mental health. A series of studies demonstrate the significant potential of psychedelics in high doses for treating effectively and with limited risk Methodologically, qualitative research based on interviews has already begun revealing a rich mosaic of user motivations, perceptions and experiences that complements and deepens the findings of the more numerous survey-based studies (Beaton et al, 2019;Johnstad 2018;Webb et al, 2019). The future inclusion of different groups of research participants would work towards a fuller understanding of the dynamic and multi-faceted development of microdosing.…”
Section: Coordinates For Sociological Investigations Of Microdosingmentioning
confidence: 99%